Contribución al conocimiento de los colorantes empleados en textiles arqueológicos colombianos. (1996)
A preiliminar dye analysis was made of sixty nine hue samples taken from fifty six precolombian textiles belonging to the Muisca, Guane, and U'wa Indians, of the Cordillera Oriental and to groups that lived in the Nariño area, dating from approximately 1000-1500 A.D. 95% of the samples were cotton and 5% were a camelid wool.